UTILIZATION OF THE SONG "LIR ILIR" TO BUILD SPIRITUAL AND MORAL AWARENESS IN 6TH GRADE STUDENTS AT AL HIKMAH ELEMENTARY SCHOOL SURABAYA - Bambang; Rokhman, Fathur; Wagiran, Wagiran; Hartono, Hartono (Journal of Social Science, 2024)
Objective: This research investigates the use of the traditional song "Lir Ilir," popularized by Sunan Kalijaga, as a teaching tool to enhance students' spiritual and moral awareness at SD Al Hikmah Surabaya. It aims to explore how integrating this cultural element into classroom activities fosters students' understanding of moral values. Method: The study employed an interactive approach by integrating "Lir Ilir" into teaching activities, including discussions of the song's meaning, group singing, art projects, and storytelling. Challenges, such as explaining the symbolism within the lyrics, were addressed through the use of visual media and in-depth explanations. Results: The implementation demonstrated that using "Lir Ilir" as a teaching tool effectively enhanced students' moral and spiritual understanding. It encouraged active participation, self-awareness, and spiritual reflection. Despite initial challenges, the innovative teaching method successfully conveyed complex philosophical ideas through engaging and meaningful experiences. Novelty: This research highlights the integration of local cultural heritage into education, emphasizing the profound potential of traditional songs like "Lir Ilir" in nurturing a strong moral foundation among students. It showcases how culturally rooted teaching methods can create impactful and reflective learning experiences while preserving heritage values.